Temporal variation in arbuscular mycorrhizal fungi colonization of bactris gasipaes kunth in buenaventura, colombia (2013)
The peach palm Bactris gasipaes is an important tropical agricultural crop cultivated for the fruits and heart of palm. We evaluated the levels of root colonization, soil spore count and morphotypes of arbuscular mycorrhizal fungi (AMF) associated with cultivated B. gasipaes in the rural areas of Citronela and Zabaletas, municipality of Buenaventura, Department of Valle del Cauca, Colombia, during three evaluation periods 2006 – 2007, to determine the influence of rainfall on the AMF colonization. The percentages of root colonization in Citronela varied between 58% and 90% while in Zabaletas root colonization varied between 63% and 79%. The average spore number in 50 g of wet soil per sample was higher in Citronela (244.6 ± 116.0 SD) compared with that in Zabaletas: 50.3 ± 24.1 SD). Twenty two morphotypes of AMF were identified from soil spores. Glomus was the most abundant mycorrhizal fungi genus in both localities, but Scutelospora was also detected. This study showed both geographic and temporal variation in mycorrhizal parameters in an important crop for the wet tropical agriculture.